TEACHER’S STRATEGY OF ISLAMIC EDUCATION IN IMPROVING LEARNING MOTIVATION AT AL-IKHLAS ISLAMIC BOARDING SCHOOL FOR TAHFIDZUL QUR’AN SUKOHARJO REGENCY - Nur Afiffah Ragilia; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2022)
This study aims to determine the condition of students’ learning motivation at Tahfidzul Qur'an Al-Ikhlas Islamic Boarding School Sukoharjo Regency, and the examine the strategy used by teacher of Islamic Education in improving learning motivation at Tahfidzul Qur’an Islamic Boarding School Sukoharjo Regency. This research used field qualitative method and phenomenology approach. The research subjects are Teacher of Islamic Educations and student representatives. Moreover, the data collection method used in this research are observation, interview, and documentation. Based on the research, it was found that learning motivation is very important, however to improve learning motivation there are several factors affecting it, they are internal and external aspects. Internal aspect covers the attitude, intelligence, norm, physical, and psychological condition of the subject. On the other hand, external aspect includes teacher, parents, friends who excels in their study, and infrastructures. Moreover, to increase learning motivation, teachers made strategies by: 1) holding a test, 2) assignment, 3) storytelling, 4) giving prizes, 5) giving punishment. In order to study the effectivity of the aforementioned learning strategy, the researcher utilized learning criteria of pembelajaran aktif (active learning), inovatif (innovative), kreatif (creative), efektif (effective), dan menyenangkan (and fun) (PAIKEM) strategy. It can be concluded that the teacher’s strategy used in the learning process is considered as less innovative and less fun.